2020
DOI: 10.1108/ijoa-07-2020-2334
|View full text |Cite
|
Sign up to set email alerts
|

The impact of equity sensitivity on mental health, innovation orientation, and turnover intention in the Hungarian and Indian contexts

Abstract: Purpose Economic turbulence brings a significant impact in the mental health of workforce on both developed and developing countries. The purpose of this paper is to explore the impact of equity sensitivity on employee mental health. Innovation is considered to be among the critical drivers for the success and future of organizational existence, therefore this paper also investigates how the equity sensitivity impacts innovation orientation and turnover intentions across two geographies India and Hungary. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
0
11
0
1
Order By: Relevance
“…For instance, factors such as age (Allen et al , 2015; Brummel and Parker, 2015; Roehling et al , 2010), education level (Roehling et al , 2010) and the life stage (Foote and Harmon, 2006) are found to modify the equity orientations. The role of gender and culture has also been explored and the findings have been largely inconclusive (Allen et al , 2005; Miller, 2009; Wheeler, 2002; Rai et al , 2020). Although there are not many studies that talk about specific cultures, categorizing the whole culture as benevolent or entitled while ignoring individual differences is not recommended.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, factors such as age (Allen et al , 2015; Brummel and Parker, 2015; Roehling et al , 2010), education level (Roehling et al , 2010) and the life stage (Foote and Harmon, 2006) are found to modify the equity orientations. The role of gender and culture has also been explored and the findings have been largely inconclusive (Allen et al , 2005; Miller, 2009; Wheeler, 2002; Rai et al , 2020). Although there are not many studies that talk about specific cultures, categorizing the whole culture as benevolent or entitled while ignoring individual differences is not recommended.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent systematic literature review, Tuli et al (2023) viewed ES with the lens of personality. Rai et al (2020) established that in the OTE personality domain, benevolent individuals have a higher attitude towards innovation. Thus, we propose the following hypothesis:…”
Section: Equity Sensitivity and Individual Ambidexteritymentioning
confidence: 99%
“…It has been argued that employee innovativeness is foundational to an organization’s success and survival (Rai et al , 2021). Innovativeness can provide a company with value-added products and services and further facilitate all aspects of the business to improve its competitiveness and performance (Ng et al , 2020).…”
Section: Introductionmentioning
confidence: 99%